Secularism, Assimilation and the Crisis of Multiculturalism French Modernist Legacies - Jansen, Yolande (IMISCOE Research, 2013)
In this timely study, Yolande Jansen critiques efforts to assimilate religious minorities into a secular and supposedly neutral public sphere. Such efforts, she ably demonstrates, can create and perpetuate the very distinctions they aim to overcome. Her sophisticated analyses draw on literature that depicts the paradoxes of assimilation as experienced by French Jews in the late nineteenth century. Paying particular attention to Marcel Proust's In Search of Lost Time, she ultimately argues for dynamic, critical multiculturalism as an alternative to secularism, assimilation, and integration.